Melatonin suppresses bone marrow adiposity in ovariectomized rats by rescuing the imbalance between osteogenesis and adipogenesis through SIRT1 activation - Xiaoxiong Huang; Weikai Chen; Chao Gu; Hao Liu; Mingzhuang Hou; Wanjin Qin; Xuesong Zhu; Xi Chen; Tao Liu; Huilin Yang; Fan He (Journal of Orthopaedic Translation, 2023)
Introduction: Accelerated imbalance between bone formation and bone resorption is associated with bone loss in postmenopausal osteoporosis. Studies have shown that this loss is accompanied by an increase in bone marrow adiposity. Melatonin was shown to improve impaired bone formation capacity of bone marrow-derived mesenchymal stem cells from ovariectomized rats (OVX-BMMSCs). Objectives: To investigate whether the anti-osteoporosis effect of melatonin involves regulation of the equilibrium between osteogenic and adipogenic differentiation of osteoporotic BMMSCs. Methods: To induce osteoporosis, female Sprague–Dawley rats received ovariectomy (OVX). Primary BMMSCs were isolated from tibiae and femurs of OVX and sham-op rats and were induced towards osteogenic or adipogenic differentiation. Matrix mineralization was determined by Alizarin Red S (ARS) and lipid formation was evaluated by Oil Red O. OVX rats were injected with melatonin through the tail vein. Bone microarchitecture was determined using micro computed tomography and marrow adiposity were examined by histology staining. Results: OVX-BMMSCs exhibited a compromised osteogenic potential and an enhanced lineage differentiation towards adipocytes. In vitro melatonin improved osteogenic differentiation of OVX-BMMSCs and promoted matrix mineralization by enhancing the expression of transcription factor RUNX2 in a dose-dependent manner. Moreover, melatonin significantly inhibited lipid formation and suppressed OVX-BMMSCs adipogenesis by down-regulating peroxisome proliferator-activated receptor γ (PPARγ). Intravenous injection of melatonin prevented bone mass reduction and bone architecture destruction in ovariectomized rats. Importantly, there was a significant inhibition of adipose tissue formation in the bone marrow. Mechanistic investigations revealed that SIRT1 was involved in melatonin-mediated determination of stem cell fate. Inhibition of SIRT1 abolished the protective effects of melatonin on bone formation by inducing BMMSCs towards adipocyte differentiation. Conclusions: Melatonin reversed the differentiation switch of OVX-BMMSCs from osteogenesis to adipogenesis by activating the SIRT1 signaling pathway. Restoration of stem cell lineage commitment by melatonin prevented marrow adipose tissue over-accumulation and protected from bone loss in postmenopausal osteoporosis. The translational potential of this article: Determination of stem cell fate towards osteoblasts or adipocytes plays a pivotal role in regulating bone metabolism. This study demonstrates the protective effect of melatonin on bone mass in estrogen-deficient rats by suppressing adipose tissue accumulation in the bone marrow. Melatonin may serve as a promising candidate for the treatment of osteoporosis in clinics.